Eating disorder behaviors as predictors of suicidal ideation among people with an eating disorder. Issue 10 (6th July 2022) - Joiner, Thomas E.; Robison, Morgan; McClanahan, Susan; Riddle, Megan; Manwaring, Jamie; Rienecke, Renee D.; Le Grange, Daniel; Duffy, Alan; Mehler, Philip S.; Blalock, Dan V.
Abstract: Objective: Suicidality is known to be elevated among people with an eating disorder. The aim of the current study was to examine whether any of three specific behavioral facets of eating disorders (i.e., purging, binge eating, restricting) would be the strongest predictors of suicidal ideation, controlling for one another, in longitudinal analyses from admission to discharge. We hypothesized that purging, above and beyond restricting or binge eating, would be the most important predictor of suicidal ideation. Method: In the present study, patients with an eating disorder ( N = 936), the majority of whom met criteria for a current DSM‐5 diagnosis of Anorexia Nervosa ( n = 560), completed the Eating Pathology Symptoms Inventory (EPSI) and the Beck Depression Inventory II‐Item 9 suicidal ideation index, at admission and again at discharge. The settings were eating disorder treatment facilities offering inpatient, residential, partial hospitalization program (PHP), and intensive outpatient (IOP) levels of care. We pitted EPSI purging, EPSI restriction, and EPSI binge eating against one another in a regression framework predicting discharge suicidal ideation controlling for suicidal ideation at admission. Results: EPSI Purging significantly predicted both presence/absence of suicidal ideation ( β = .22, t = 2.48, p = .01; OR = 1.25, 95% CI [1.05, 1.49]) and intensity of suicidal ideation ( β = .04, t = 2.31, p = .02) at discharge, whereas neither EPSI Restricting nor EPSI Binge Eating did (p > .30). Discussion: Study results suggest that purging may have particular relevance in estimating suicide risk in patients with an eating disorder.